Best Answer

There are two steps to the process:

Step-1:

Subtract 7 from 6. The answer to this step is -1.

Remember that as you proceed to the next step.

Now, go on to the next step.

Step-2:

Take the -1 from the first step, and add 5 to it.

The new result is then +4 .

The +4 that you have now is the value of the entire original expression.

🙏

🤨

😮

Study guides

Q: How do you evaluate 6-7 plus 5?

Write your answer...

Submit

Related questions

67 + 5 = 72

(-11) + (-89) + 5 + (-67) + (-81) + (-27) = -270

Evaluate 9p + 33 for p = 5

67 plus 67 plus 67 is equal to 201.

5 + 62 = 67

no it = 10

82

3+6+7+89+4+5+7+9+90+67 = 287

67

3

194

5 - 2 + 11 = 14

Evaluate -4(a+b) - 10a/b when a=8 and b=5

525. 5 + 4 = 9 + 67 = 73 + 98 = 171 + 12 = 183 + 34 = 217 + 11 = 229 + 51 = 280 + 90 = 370 + 47 = 417 + 8 = 525.

67 + 112 + 55 = 234

67 plus 3 equals 70.

The expression cannot be evaluated without knowing the value of m.

48 + 67 + 134 + 121 + 15 = 385

67+8+9+42 = 126

67 + 3 + 3 = 73

100 + 27 - 52 + 67 + 92 = -84

45 - 78 + 67 + 1904 + 6879 = -8,883

67 + 536 = 603

88 + 67 = 155

35 + 67 = 102